1996
DOI: 10.1107/s0907444995014302
|View full text |Cite
|
Sign up to set email alerts
|

An Eye Lens Protein–Water Structure: 1.2 Å Resolution Structure of γB-Crystallin at 150 K

Abstract: Abstract7B-crystallin is a structural protein of the eye lens with a role in the maintenance of an even distribution of protein and water over distances around the wavelength of light, preserving lens transparency. The structure of the 174-residue bovine protein has already been determined at room temperature to 1.47 A resolution. By flash freezing the protein crystals, data have now been collected to a nominal resolution limit of 1.2 A as radiation damage was essentially eliminated. The protein-water model ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 25 publications
4
33
0
Order By: Relevance
“…A fraction of the protein crystals which diffract to atomic resolution contain only a very small region of disordered solvent. Two examples of this are crambin (Stec et al, 1995;Teeter, 1992) and B-crystallin (Kumaraswamy et al, 1996). In these structures, virtually all the water molecules making up the solvent volume of the crystal are well ordered and are therefore explicitly present in the structural model.…”
Section: Anisotropy Of Water Molecules Associated With the Protein Stmentioning
confidence: 99%
“…A fraction of the protein crystals which diffract to atomic resolution contain only a very small region of disordered solvent. Two examples of this are crambin (Stec et al, 1995;Teeter, 1992) and B-crystallin (Kumaraswamy et al, 1996). In these structures, virtually all the water molecules making up the solvent volume of the crystal are well ordered and are therefore explicitly present in the structural model.…”
Section: Anisotropy Of Water Molecules Associated With the Protein Stmentioning
confidence: 99%
“…12 and described there; briefly, d 11 corresponds to the diameter of a sphere with the volume of one molecule of γB-crystallin. With use of the value for γB-crystallin 5 of v eff = 0.71 cm 3 /g, typical of globular proteins, together with the known molecular weight M W ,γ of bovine γB-crystallin, 20 993 g/mol, 58 one obtains d 11 = 36.2 Å. However, the sticky-sphere model light scattering predictions can be written so that the diameter values enter in terms of ratios, and so we take d 11 = 1 in Table I.…”
Section: A Molecular Parameters For γB and α-Crystallinmentioning
confidence: 99%
“…In those works, X-ray data were sometimes collected at freezing temperature to reduce the irradiation damage of crystals and to extend the resolution. [13][14][15] On the other hand, Sevcik et al 16 have reported the refinement of ribonuclease at atomic resolution using the data measured at room temperature. In the present paper, we deal with crystals of two chicken type lysozymes, turkey egg lysozyme (TEL) and human lysozyme (HL).…”
Section: Introductionmentioning
confidence: 98%